Experimental dynamic behavior of free standing multi-block structures under seismic loadings - Peña, Fernando (2008)
This paper describes the dynamical behavior of free standing block structures under seismic loading. A comprehensive experimental investigation has been carried out to study the rocking response of four single blocks of different geometry and associations of two and three blocks. The blocks, which are large stones of high strength blue granite, were subjected to free vibration, and harmonic and random motions of the base. In total, 379 tests on a shaking table were carried out in order to address the issues of repeatability of the results and stability of the rocking motion response. Significant understanding of the rocking motion mechanism is possible from the high quality experimental data. Extensive experimental measurements allowed to discuss the impulsive forces acting in the blocks and the three-dimensional effects presented in the response.